2011
DOI: 10.1038/onc.2011.100
|View full text |Cite
|
Sign up to set email alerts
|

ARF1 controls proliferation of breast cancer cells by regulating the retinoblastoma protein

Abstract: The ADP-ribosylation factors (ARFs) 1 and 6 are small GTP-binding proteins, highly expressed and activated in several breast cancer cell lines and are associated with enhanced migration and invasiveness. In this study, we report that ARF1 has a critical role in cell proliferation. Depletion of this GTPase or expression of a dominant negative form, which both resulted in diminished ARF1 activity, led to sustained cell-growth arrest. This cellular response was associated with the induction of senescent markers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 56 publications
1
38
0
1
Order By: Relevance
“…Since several Arfs like Arf1, Arf4 and Arf6 regulate integrin trafficking, it is not surprising that they have an impact on the migratory and invasive capacities of cancer cells. Indeed, it has been demonstrated that Arf1 controls cell migration and proliferation of breast cancer cells 26 . Arf1 interacts with β1-integrin and regulates the interaction between this integrin and key proteins of FAs, such as paxillin, talin and FAK (Fig.…”
Section: Arf Family Proteins In Integrin Internalization and Recyclingmentioning
confidence: 99%
“…Since several Arfs like Arf1, Arf4 and Arf6 regulate integrin trafficking, it is not surprising that they have an impact on the migratory and invasive capacities of cancer cells. Indeed, it has been demonstrated that Arf1 controls cell migration and proliferation of breast cancer cells 26 . Arf1 interacts with β1-integrin and regulates the interaction between this integrin and key proteins of FAs, such as paxillin, talin and FAK (Fig.…”
Section: Arf Family Proteins In Integrin Internalization and Recyclingmentioning
confidence: 99%
“…We have recently found that ARF1 regulates the activation of the Raf1/MEK/ERK1/2 pathway by α 2B -adrenergic receptor, a prototypic G protein-coupled receptor (GPCR) [20]. In cancer biology, ARF1 has been shown to regulate proliferation and migration of breast cancer cells which is mediated through the phosphoinositide 3-kinase (PI3K) pathway [21], the retinoblastoma protein [22] and Rac1 [23]. Interestingly, AMF-26, a small molecule octahydronaphthalene derivative, inhibits ARF1 activation and induces complete regression of human breast cancer BSY-1 xenografts [24].…”
Section: Introductionmentioning
confidence: 99%
“…Because ARF1 controls migration and proliferation (Boulay et al. , 2008, 2011), we reasoned that this ARF isoform is also a key signaling effector regulating invasion. Here we demonstrate that modulation of ARF1 expression levels and activity leads to impaired invasive capacities of MDA-MB-231 cells through invadopodia maturation and shedding of microvesicles.…”
Section: Introductionmentioning
confidence: 99%